2017
DOI: 10.1007/s12306-017-0494-8
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral and scapulohumeral kinematic analysis of patients with traumatic anterior instability wearing a shoulder brace: a prospective laboratory study

Abstract: The immobilizer significantly limited joint excursion in all planes of movement except internal rotation. The narrower humeral head translation with respect to the trunk, measured in the tests with the brace, demonstrates that the immobilizer achieves the goal of preserving joint stability in the movements that are at risk of dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Similarly, Mcleod et al 26 investigated 4 shoulder braces (SAWA shoulder brace, Sully brace, SaundersGroup; Douglas shoulder sling, Douglas Protective Equipment), and a homemade elastic restraint (shoulder strap) and found that all 4 braces, again, initially limited active shoulder ROM but loosened after exercise, resulting in a significant increase in active shoulder abduction and external rotation. Dellabiancia et al, 14 in a prospective laboratory study investigating shoulder joint excursion while wearing the S2 Shoulder Stabilizer (Dual Sanitaly SpA), demonstrated significantly limited joint excursion in all planes of movement, except internal rotation, as well as narrower humeral head translation. The authors concluded that the S2 Shoulder Stabilizer improves joint stability during movements that are at risk for dislocation.…”
Section: Biomechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Mcleod et al 26 investigated 4 shoulder braces (SAWA shoulder brace, Sully brace, SaundersGroup; Douglas shoulder sling, Douglas Protective Equipment), and a homemade elastic restraint (shoulder strap) and found that all 4 braces, again, initially limited active shoulder ROM but loosened after exercise, resulting in a significant increase in active shoulder abduction and external rotation. Dellabiancia et al, 14 in a prospective laboratory study investigating shoulder joint excursion while wearing the S2 Shoulder Stabilizer (Dual Sanitaly SpA), demonstrated significantly limited joint excursion in all planes of movement, except internal rotation, as well as narrower humeral head translation. The authors concluded that the S2 Shoulder Stabilizer improves joint stability during movements that are at risk for dislocation.…”
Section: Biomechanicsmentioning
confidence: 99%
“…The authors concluded that the S2 Shoulder Stabilizer improves joint stability during movements that are at risk for dislocation. 14…”
Section: Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are not practical for overhead throwing athletes or for athletes with injuries to the dominant shoulder. Instead, less restrictive neoprene sleeves may be considered 42 . Additional and higher-level studies are needed to assess the efficacy of prophylactic sports bracing to prevent recurrent instability in athletes.…”
Section: Sports Brace Usementioning
confidence: 99%
“…Due to this high rate or recurrence, athletes should take steps to reduce risks such as: warming up their muscles adequately prior to activity, not participating if normal function is compromised and, wearing a brace in cases of recurrent shoulder instability ("Gunderson Clinic", n.d.). Dellabiancia et al (2017) used VICON TM motion capture technology to measure the range of motion of the glenohumeral joint of athletes suffering from anterior shoulder instability with, and without, a brace being worn. The group concluded that "the immobilizer achieves the goal of preserving joint stability in the movements that are at risk of dislocation" (Dellabiancia, et al, 2019, p. S159) after observing reduced range of motion when the brace was worn.…”
mentioning
confidence: 99%